The deep end ebook - Kinney, Jeff (Diary of a Wimpy Kid, 2020)
An instant #1 USA Today , Wall Street Journal , and New York Times bestseller! In The Deep End , book 15 of the Diary of a Wimpy Kid series from #1 international bestselling author Jeff Kinney, Greg Heffley and his family hit the road for a cross-country camping trip, ​ready for the adventure of a lifetime. But their plans hit a major snag, and they find themselves stranded at an RV park that's not exactly a summertime paradise. Things only get worse for the Heffleys when the skies open up and the water starts to rise, making them wonder if they can save their vacation—or if they're already in too deep. Collect all the books in the #1 bestselling Diary of a Wimpy Kid series: Diary of a Wimpy Kid (#1) | Rodrick Rules (#2) | The Last Straw (#3) | Dog Days (#4) | The Ugly Truth (#5) | Cabin Fever (#6) | The Third Wheel (#7) | Hard Luck (#8) | The Long Haul (#9) | Old School (#10) | Double Down (#11) | The Getaway (#12) | The Meltdown (#13) | Wrecking Ball (#14) | The Deep End (#15) | Big Shot (#16) | Diper Överlöde (#17) | No Brainer (#18) | Hot Mess (#19) See the Wimpy Kid World in a whole new way with the #1 bestselling Awesome Friendly books, told from the perspective of Greg Heffley's best friend Rowley Jefferson: Diary of an Awesome Friendly Kid: Rowley Jefferson's Journal | Rowley Jefferson's Awesome Friendly Adventure | Rowley Jefferson's Awesome Friendly Spooky Stories